Assessment of Disaster Preparedness Parameters and Disaster Resilience Measures for Local Government Results-Based Monitoring and Evaluation - Lorenzo, Evelyn S. (Journal in Urban and Regional Planning, 2024)
The 2015 Sendai Framework for Disaster Risk Reduction (SFDRR) calls for a more robust assessment of local disaster risk reduction efforts against resiliency targets to foster greater accountability in building resilience. However, resilience is a complex concept that does not neatly square with accountability. Often, it challenges established disaster risk management (DRM) performance assessments due to diverse interpretations and analytical measures. This study examined the Department of Interior and Local Government (DILG) annual Disaster Preparedness Audit (DPA) and its potential to measure resilience. It compared current disaster preparedness parameters against widely applied measures of disaster resilience. Different concepts of community resilience and assessment models surfaced conceptual and methodological requisites that can benefit the DPA model. The DILG and other DRM agencies validated the results, which point to the absence of a common analytical language and the high mutability of performance metrics that lack a logical structure. Findings suggest that local governments mediate community risk reduction through a network-driven approach. Further collective risk management strategies can be contractible despite their diversity, provided these are structured to deliver minimum measurable results. This study recommends a conceptual boundary for local government resilience and the operational considerations to inform the configuration of current assessment practices for Local Government Unit (LGU) disaster preparedness while fostering accountability.